Effects of microwave pretreatment on sago hampas for glucose production - Nursyamnas, Binti Shari (Universiti Malaysia Sarawak, UNIMAS, 2013)
Sago hampas was considered as waste from sago palm industry in Sarawak. Composition of dried sago was mainly starch and fiber components. This research investigated the effects of microwave pretreatment on acid and enzyme hydrolysis. It is also to determine the glucose production after hydrolysis process. Two concentration of sulphuric acid, 0.5% and 1.0%, were used in dilute acid hydrolysis whereas the enzymatic hydrolysis were conducted using amyloglucosidase at 60ºC. Changes on sago hampas structures after pretreatment and hydrolysis was observed by Scanning Electron Microscopy. The concentration of glucose produced after pretreatment by microwave and hydrolysis was analysed using High Performance Liquid Chromatography. Dilute acid was able to hydrolysed the starch into glucose. The production of glucose increased after microwave treatment but higher concentration of dilute acid restricted the glucose production. Overall, microwave heating has improved the production of glucose after dilute acid treatment and enzyme hydrolysis treatment.